Association between poor sleep quality and depression symptoms among the elderly in nursing homes in Hunan province, China: a cross-sectional study. Issue 7 (13th July 2020) - Hu, Zhao; Zhu, Xidi; Kaminga, Atipatsa Chiwanda; Zhu, Tingting; Nie, Yu; Xu, Huilan
Abstract : Objectives: To examine the association between the prevalence of poor sleep quality and depression symptoms among the elderly in the nursing homes of Hunan province in China. Design, Setting and participants: This was a cross-sectional study investigating 817 elderly people from 24 nursing homes in China's Hunan province. Main outcome measures: Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) such that poor sleep quality was defined as PSQI Score >5. In addition, depression symptoms were assessed using the Geriatric Depression Scale (GDS). Linear regression models and binary logistic regression models were used to analyse the relationship between the prevalence of poor sleep quality and depression symptoms. Results: The mean PSQI Score was 8.5±4.9, and the prevalence of poor sleep quality was 67.3%. Additionally, the mean GDS Score was 9.8±7.5, and the prevalence of depression symptoms was 36.0%. Elderly people with poor sleep quality had increased GDS Score (mean difference=2.54, 95% CI 1.66 to 3.42) and increased risk of depression symptoms (OR=3.19, 95% CI 2.04 to 4.98) after controlling for demographics, chronic disease history, lifestyle behaviours, social support, activities of daily living and negative life events. Conclusions: The prevalence of poor sleep quality was relatively high, and this was associated with increased depression symptoms. Therefore, poor sleep quality could be speculated as a marker of current depression symptoms in the elderly.